A posteriori error estimates for discontinuous Galerkin methods of obstacle problems. (April 2015) - Wang, Fei; Han, Weimin; Eichholz, Joseph; Cheng, Xiaoliang
Abstract: We present a posteriori error analysis of discontinuous Galerkin methods for solving the obstacle problem, which is a representative elliptic variational inequality of the first kind. We derive reliable error estimators of the residual type. Efficiency of the estimators is theoretically explored and numerically confirmed.